Synthesis and Structural Characterization of Diiron Dithiolate Complex [(μ-SCH2)2NCH2PhFe2(CO)5]2(Ph2PCH2CH2CH2PPh2) with Bridging Diphosphine Ligand - Gao, Wei; Tian, Lian-Qi; Yang, Jing (Asian Journal of Chemistry, 2014)
A novel diiron dithiolate complex [(μ-SCH2)2NCH2PhFe2(CO)5]2(Ph2PCH2CH2CH2PPh2) (1), as the active site model of [FeFe]-hydrogenases, has been prepared and structurally characterized. The title complex could be prepared by reaction of [(μ-SCH2)2NCH2Ph]Fe2(CO)6 (A) with 1,3-bis(diphenylphosphinopropane) (DPPP) (Ph2PCH2CH2CH2PPh2) in the presence of Me3NO·2H2O in MeCN at room temperature in 54 % yield. The new complex 1 was characterized by IR, 1H NMR and 31P NMR spectroscopy.